Economic value of dung removal by dung beetles in US sub-tropical pastures - Stanbrook-Buyer, Roisin; Bhat, Mahadev; King, Joshua R. (Basic and applied ecology, 2024)
In livestock management systems, the rapid removal of cattle dung by dung beetles plays an essential role in returning areas of pasture to grazing which normally would be lost because of dung contamination. Thus, dung removal is an ecosystem process with established links to services with potentially valuable outcomes. We focused on dung removal under two dung beetle abundance scenarios. We then calculated the economic value of dung beetle action on dung degradation in US sub-tropical pasturelands under each scenario by measuring the costs associated with restriction of new forage growth by dung pat smothering, and the amount of forage gained because of dung beetle mediated dung decomposition. We found if dung is left unmanipulated by dung beetles, it would naturally decompose at an average rate of 3.75 g per day, and dung in pastures with a high abundance of dung beetles would decay at 10.73 g per day. We show the economic benefit of dung decomposition under each scenario is directly related to both the presence and abundance levels of dung beetles in cattle pastures, for instance, resulting in additional grass area to become available to raise 1,131 cows and 1,676 cows under low dung beetle abundances and under high dung beetle abundances, respectively. This amounts to an additional income of USD 918,688 per year in Florida sub-tropical livestock systems containing low abundances of dung beetles and an income of USD 1,360,770 per year for pastures sustaining a higher abundances of dung beetles. Despite their importance in livestock systems dung beetle populations are imperiled by the widespread use of agrochemicals. Reducing agrochemical usage and introducing biodiversity-friendly practices in livestock systems will be important for conserving dung beetles and the ecological functions that dung beetles provide in working landscapes.